Strengthening Health System Resilience Through Governance Reform - Sirojuddin Abror; Hawwin Muzakki (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The COVID-19 pandemic exposed critical structural weaknesses in global health systems and underscored the importance of effective governance in sustaining progress toward Universal Health Coverage (UHC). This study presents a cross-national comparative analysis of five countries New Zealand, South Korea, Germany, the United States, and Brazil to evaluate how governance dynamics influenced health system resilience and the trajectory toward UHC during the pandemic. Employing a mixed-methods research design, the study integrates policy reviews, public health data, and expert interviews to assess four key governance dimensions: response speed, policy coherence, public trust, and enforcement effectiveness. The results reveal that countries with responsive and transparent governance structures were better able to maintain essential health services, safeguard vulnerable populations, and ensure equitable access without imposing significant financial burdens. Conversely, nations with fragmented or incoherent policy environments experienced greater disruptions and setbacks in their UHC pathways. The study concludes that governance reform must be positioned as a strategic imperative not merely an administrative function in global health planning. Strengthening cross-sectoral coordination, enhancing data transparency, and building institutional trust are essential for constructing health systems that are not only resilient to future crises but also inclusive and equitable in the pursuit of UHC.